2013
DOI: 10.1111/j.1365-2125.2012.04450.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blueberry juice on clearance of buspirone and flurbiprofen in human volunteers

Abstract: AIMThe present study evaluated the possibility of drug interactions involving blueberry juice (BBJ) and substrate drugs whose clearance is dependent on cytochromes P4503A (CYP3A) and P4502C9 (CYP2C9). METHODSA 50:50 mixture of lowbush and highbush BBJ was evaluated in vitro as an inhibitor of CYP3A activity (hydroxylation of triazolam and dealkylation of buspirone) and of CYP2C9 activity (flurbiprofen hydroxylation) using human liver microsomes. In clinical studies, clearance of oral buspirone and oral flurbip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The principal statistical method was Student's paired t‐test. C max and AUC values from fed and fasted conditions were further compared using procedures for bioequivalence testing and drug interaction studies …”
Section: Methodsmentioning
confidence: 99%
“…The principal statistical method was Student's paired t‐test. C max and AUC values from fed and fasted conditions were further compared using procedures for bioequivalence testing and drug interaction studies …”
Section: Methodsmentioning
confidence: 99%
“…9 In addition to grapefruit juice, flavonoids present in oranges and apples have also been shown to reduce the activity of the organic acid transporter OATP2B1. 8 Although the grapefruit juice-CYP3A4 substrate interaction and the potential for producing significant nutrient-drug interactions is the most well characterized, it should be noted that, in addition to inhibiting CYP3A4 activity, cranberry, pomegranate, and blueberry juice can inhibit the activity of CYP2C9, 10,12 a cytochrome P450 isoform that catalyzes the biotransformation of therapeutic drugs such as ibuprofen, flurbiprofen, warfarin, phenytoin, fluvastatin, and amitriptyline. The clinical significance of any of the aforementioned juice-drug interactions is extremely difficult to predict on the basis of a history of coingestion.…”
Section: Pharmacologic Considerations Associated With Fruit Juice Ingmentioning
confidence: 99%
“…66 Regarding CYP3A-mediated fruit juice-drug interaction, although both lime juice and blueberry juice demonstrated an inhibitory effect on CYP3A activity in vitro, 67,68 both of them showed negative results in vivo when they were evaluated with felodipine and buspirone, respectively, in 2 independent clinical studies. 67,68 However, it should be noted that the lime juice evaluated in vivo was a diluted one (onequarter strength), and although mean felodipine exposure was not changed in the presence of dilute lime juice, the magnitude of felodipine increase was correlated with that observed with grapefruit juice among individuals (r 2 ¼ 0.95). 68 In addition, Kim et al 69 evaluated the effects of various fruit juices on the activity of midazolam 1 0 -hydroxylase, a marker of CYP3A, in pooled human liver microsomes.…”
Section: Cyp3a-mediated Beverage-drug Interactionmentioning
confidence: 98%
“…In vitro mechanistic studies indicated that Seville (sour) orange juice decreased intestinal CYP3A protein concentration and therefore might inhibit CYP3A by the same mechanism as GFJ . Regarding CYP3A‐mediated fruit juice–drug interaction, although both lime juice and blueberry juice demonstrated an inhibitory effect on CYP3A activity in vitro, both of them showed negative results in vivo when they were evaluated with felodipine and buspirone, respectively, in 2 independent clinical studies . However, it should be noted that the lime juice evaluated in vivo was a diluted one (one‐quarter strength), and although mean felodipine exposure was not changed in the presence of dilute lime juice, the magnitude of felodipine increase was correlated with that observed with grapefruit juice among individuals ( r 2 = 0.95) .…”
Section: Cyp3a‐mediated Beverage–drug Interactionmentioning
confidence: 99%